PREPARATION OF COOPERATIVE LEARNING SCENARIO TYPE OF SNOWBALL THROWING AS AN EFFORT TO IMPROVE LEARNING QUALITY IN SDN 001 MUARA LEMBU - Desmalina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
One of the roles of the teacher is as a planner. But the fact is that the teacher has not managed the planning well. This study aims to improve the quality of learning through guidance in developing snowball throwing cooperative learning scenarios for elementary school teachers. This study was conducted at SDN 001 Muara Lembu from October to November 2019. The research subjects were 12 SDN 001 Muara Lembu teachers. This research is a school action research design based on the Kemmis model. The expected indicator of success is that the quality of learning reaches good categories. The results of the study in the first cycle are the average quality of learning to get a value of 61% which includes enough categories, in the second cycle increased to 77% which is classified as good. The conclusion based on the results is that the quality of learning has improved after the guidance of SDN 001 Muara Lembu teachers in developing snowball throwing cooperative learning scenarios.